2004
DOI: 10.1002/sia.1879
|View full text |Cite
|
Sign up to set email alerts
|

XPS analysis of electronic density of iron tetraazamacrocycle through Fe 2p binding energies on the 3‐imidazolilpropyl‐modified surface of oxidized n‐Si(100)

Abstract: This paper describes the preparation of metallo-organic thin films of [FeTIM(CH 3 CN) 2 ]2+ complex, where TIM stands for 2,3,9,10-tetramethyl-1,4,8,11-tetraazacyclotetradeca-1,3,8,10-tetraene on oxidized silicon wafer, SiO 2 /Si, previously treated with 3-imidazolilpropyltrimethoxysilane, 3-IPTS. X-ray photoemission lines of Fe 2p were used to probe the iron chemical environment in the physically and chemically adsorbed macrocycle complexes. As FeTIM can bind CO, NO or N-heterocycle, a built-on Si wafer senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…[91,92] This stability, together with the versatility of possible applications and the evident biological relevance, has stimulated various studies about these compounds. Macrocycles have been employed in surface modification (thin films), [93,94] supramolecular systems (super molecules), [95,96] reconstitution of haemoproteins, [97][98][99] model complexes of haemoproteins, biosensors, and others. [100,101]…”
Section: Porphyrins and Phthalocyanines: Macrocycle Compoundsmentioning
confidence: 99%
“…[91,92] This stability, together with the versatility of possible applications and the evident biological relevance, has stimulated various studies about these compounds. Macrocycles have been employed in surface modification (thin films), [93,94] supramolecular systems (super molecules), [95,96] reconstitution of haemoproteins, [97][98][99] model complexes of haemoproteins, biosensors, and others. [100,101]…”
Section: Porphyrins and Phthalocyanines: Macrocycle Compoundsmentioning
confidence: 99%
“…5, which was fitted with two components at 399.7 and 401.9 eV, assigned to nonprotonated and protonated imidazole groups, respectively. The protonation could result either from the interaction between the bent 3-IPTS and the surface silanol groups with a consecutive proton transfer [14,15,22], or from the reaction with the hydrogen chloride obtained as a by-product from the reaction of 3-ClPTS and imidazole, or by proton transfer from adlayer water.…”
Section: -Iptsmentioning
confidence: 99%
“…Although the two-step procedure reported by Andresa et al [14] has shown higher surface yields, our attention has been devoted to the one-pot method, as it is an easier and more reliable procedure. Fig.…”
Section: -Iptsmentioning
confidence: 99%
See 2 more Smart Citations